Dreamers and deceivers : true stories of the heroes and villains who made America - Beck, Glenn; Balfe, Kevin (Threshold Editions/Mercury Radio Arts, 2014)
"Glenn Beck provides stories of the people who [in his view] built America and the people who sought to destroy it"--